Microplastics in soil can increase nutrient uptake by wheat - Liu, Yuhuai; Xiao, Mouliang; Shahbaz, Muhammad; Hu, Zhi’e; Zhu, Zhenke; Lu, Shunbao; Yu, Yongxiang; Yao, Huaiying; Chen, Jianping; Ge, Tida (Journal of hazardous materials, 2022)
Microplastics can perturb microbial nutrient-mining strategies. However, the mechanism by which microplastics affect the resource-acquisition strategies of crops in agricultural systems remains unknown. The nutrient-acquisition potential of crops and microbes was investigated under treatments with two common microplastics (polyethylene [PE] and polyvinyl chloride [PVC]) at 0%, 1%, and 5% (w/w). Different root resource-acquisition strategies disturbed microbial nutrient turnover in the rhizosphere in response to microplastic addition. Specifically, the β-1,4-glucosidase (BG) hotspot expanded, whereas the rhizosphere expansion of BG activity decreased. A decrease of less than PE1% (w/w) and an expansion of less than PE5% (w/w) in the 1,4-N-acetyl-glucosaminidase (NAG) hotspot with wider rhizosphere expansion of NAG activity indicated that higher doses of PE allow roots to uptake additional N. The phosphomonoesterase (PHOS) hotspot decreased in PE1% (w/w) and expanded in PE5% (w/w), but rhizosphere expansion did not change under PE treatments. However, both NAG and PHOS hotspots expanded with decreasing rhizosphere expansion under PVC treatments, indicating that PVC limits the utilization of available N and P, forcing the crop to obtain nutrients from the narrow root zone. These results indicate that adding PE microplastics increases the demand for and consumption of NH4+-N and NO3--N by wheat. [Display omitted] •Different root resource-acquisition strategies disturb microbial nutrient turnover.•Higher doses of polyethylene (5% (w/w)) enable roots to uptake additional N.•PVC cannot lead to microbial SOM decomposition for N and P acquisition.•PVC forced wheat to efficiently obtain available nutrients in the narrow root zone.